Simultaneous genotyping for human platelet antigen systems and HLA-A and HLA-B loci by targeted next-generation sequencing - Wang, Jielin; You, Xuan; He, Yanmin; Hong, Xiaozhen; He, Ji; Tao, Sudan; Zhu, Faming (Frontiers in Immunology, 2022)
In order to treat the alloimmunization platelet transfusion refractoriness (PTR), it usually used the HLA-type and/or HPA-type match platelet between the donors and patients. Therefore, genotyping of HLA-A, -B loci and HPA systems for the donors and patients is of great significance. However, there is a rare report about simultaneously genotyping for HLA-A, -B loci and HPA systems. In this study, a high-throughput method for simultaneous genotyping HLA-A, -B loci and HPA genotyped is developed. A RNA capture probe panel covering all exon sequences of the GP1BA, GP1BB, ITGA2, CD109, ITGB3, ITGA2B genes and HLA-A, -B loci was designed. The HLA-A, -B and 34 HPA systems were genotyped using a targeted next-generation sequencing (NGS) method. The genotype of HLA-A, -B loci and HPA was assigned according to the nucleotides in the polymorphism sites. 204 unrelated blood specimens were successfully genotyped for all 34 HPA systems and HLA-A, -B loci using the NGS method. The accuracy of the NGS method was 100%. Only HPA-2, 3, 5, 6w, 15 and 21w systems were showed polymorphism with the frequency 0.9412, 0.6863, 0.9853, 0.9779, 0.4314 and 0.9951 for a allele respectively. Thirty-two single nucleotide variants (SNVs) were detected. Of them, 12 SNVs can lead to the amino acids change. HLA-A*11:01 and HLA-B*46:01 are the most common alleles for HLA-A and B loci. A targeted next-generation sequencing method for simultaneously genotyping for HPA systems and HLA-A, -B loci was first established, which could be applied for establish the database for HLA-typed and/or HPA-typed unrelated donors.